Artificial Caries Resistance in Enamel after Topical Fluoride Treatment and 445 nm Laser Irradiation. (3rd November 2019) - Al-Maliky, Mohammed Abbood; Frentzen, Matthias; Meister, Jörg
Abstract : Objective . This in vitro study is aimed at investigating the caries preventive effectiveness of 445 nm diode laser in combination with topical fluoridation. Materials and methods . A total of 30 caries-free bovine teeth were used in this study. Eighteen teeth were covered with nail varnish except four windows on the labial surface. The windows were assigned to no treatment/control (C), laser (L) (0.3 W, 60 s, and 90 J/cm 2 ), fluoride (F), and fluoride followed by laser (FL) treatment groups. Artificial caries lesions were created, and the teeth were sectioned and investigated under polarized light microscopy for quantitative measurement of the resulted lesion depth. Ten teeth were used for surface temperature measurement and two teeth for scanning electron microscopy (SEM). Extra twelve human molars were used for the intrapulpal temperature measurement. The absorbance of fluoride at 445 nm was measured. Results . The means of lesion depth for the C, L, F, and FL groups were 123.48 (±21.93), 112.33 (±20.42), 99.58 (±30.68), and 89.03 (±30.38) μ m, respectively. The pairwise differences of the L, F, and FL groups compared with the C group were significant (p < 0.05 ). The differences between groups were tested: FL versus L p = 0.02, F versus L p = 0.16, and FL versus F p = 0.91, and the difference of the F versus FL was not significant (p = 0.91 ). Temperature increment at the enamel surface and pulp roof were ∆ T  = 16.67 (±4.11) and 2.12 (±0.66)°C, respectively. The topical fluoride absorbance at 445 nm is five orders higher than that at 810 nm. SEM shows that after laser irradiation the enamel surface was intact and without thermal damage. Conclusions . The 445 nm laser irradiation may be useful for caries prevention, and its effectiveness is lower than those previously achieved using the argon ion laser.